Noninvasive characterization of graft steatosis after liver transplantation. (February 2014) - Karlas, Thomas; Kollmeier, Johanna; Böhm, Stephan; Müller, Jürgen; Kovacs, Peter; Tröltzsch, Michael; Weimann, Antje; Bartels, Michael; Rosendahl, Jonas; Mössner, Joachim; Berg, Thomas; Keim, Volker; et al.
Abstract Objective. Liver graft steatosis has not been noninvasively evaluated yet. We therefore characterized liver transplant recipients by transient elastography (TE) and controlled attenuation parameter (CAP) and correlated the results with clinical and genetic risk factors. Methods. A total of 204 patients (pretransplant disease: n = 102 nonalcoholic etiology, nonalcoholic liver cirrhosis (non-ALC); n = 102 alcoholic liver disease, ALC; 42% female; median age 57.8 years; median time since transplantation 66 months) underwent ultrasound, TE, CAP, and nonalcoholic fatty liver disease (NAFLD) fibrosis score. Recipient DNA samples were genotyped for patatin-like phospholipase domain-containing protein 3 (PNPLA3) (rs738409) and IL28B (rs8099917, rs12979860) polymorphisms. Results. Increased hepatic echogenicity at ultrasound was observed in 36% of patients, CAP values >252 and >300 dB/m indicated steatosis and advanced steatosis in 44% and 24% of individuals. Advanced fibrosis (TE >7.9 kPa) was associated with increased CAP results (266 vs. 229 dB/m, p = 0.012). PNPLA3 G-allele carriers had increased CAP values (257 vs. 222 dB/m, p = 0.032), higher liver stiffness (TE 6.4 vs. 5.5 kPa, p = 0.005), and prevalence of diabetes mellitus (40% vs. 22%, p = 0.016). No such association was observed for IL28B polymorphisms. ALC compared to non-ALC patients had higher body mass index (28.1 vs. 25.5 kg/m², p < 0.001), higher prevalence of diabetes mellitus (41% vs. 25%, p = 0.017), and PNPLA3 CG + GG genotype (73% vs. 47%, p = 0.006), and had elevated TE (6.3 vs. 5.4 kPa, p = 0.022), CAP (266 vs. 221 dB/m, p = 0.001), and NAFLD fibrosis score (score −0.5 vs. −1.3, p < 0.001). Conclusion. Modern noninvasive liver graft assessment frequently detects hepatic steatosis, which is associated with graft fibrosis, components of the metabolic syndrome and recipient PNPLA3 rs738409 genotype, especially in ALC patients.